Pharmacokinetics of liposomal curcumin (Lipocurc™) infusion: effect of co-medication in cancer patients and comparison with healthy individuals - Bolger, Gordon T.; Licollari, Albert; Tan, Amin; Greil, Richard; Vcelar, Brigitta; Greil-Ressler, Sigrun; Weiss, Lukas; Schönlieb, Charlotte; Magnes, Teresa; Radl, Bianca; Majeed, Muhammed; Sordillo, Peter P. (Cancer chemotherapy and pharmacology, 2019)
Purpose Investigation of the impact of co-medication on the plasma levels of curcumin and tetrahydrocurcumin (THC) in cancer patients and a comparison of the pharmacokinetics of curcumin and plasma levels of THC between cancer patients and healthy individuals following intravenous infusion of Lipocurc™ (liposomal curcumin). Methods Correlation analysis was used to determine the impact of co-medication on infusion rate normalized plasma levels of curcumin and THC in cancer patients and to compare the plasma levels of curcumin and THC at different infusion rates between cancer patients and healthy individuals. In vitro hepatocyte and red blood cell distribution experiments were conducted with Lipocurc™ to support clinical findings. Plasma concentration time data were analyzed by the non-compartmental method to determine and compare the pharmacokinetic parameters of curcumin in cancer patients and healthy individuals. Results Of 44 co-medications studied, three medications targeting the renin–angiotensin system, Lisinopril, Ramipril, and Valsartan elevated plasma levels of curcumin and THC in three cancer patients infused with Lipocurc™. Cell distribution experiments indicated that the disposition of curcumin in red blood cells may be a target for elevation of the plasma levels of curcumin. Plasma levels of curcumin in cancer patients increased to a greater extent with increased infusion rate compared to healthy individuals. Upon termination of infusion, the elimination phase for curcumin was shorter with a shorter terminal half-life and smaller volume of distribution for curcumin in cancer patients compared to healthy individuals. Conclusion Either co-medications or health status, or both, can impact the pharmacokinetics of curcumin infusion (as Lipocurc™) in cancer patients.